ANALISIS PENGARUH BUDAYA ORGANISASI, PENGEMBANGAN KARIR DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PEGAWAI DINAS PERUMAHAN RAKYAT KAWASAN PERMUKIMAN DAN CIPTA KARYA KABUPATEN SUMENEP - Muchammad Yunus; Indra Prasetyo; Muninghar (Fakultas Ekonomi Universitas 45 Surabaya, 2021)
The purpose of this study are : 1) describe the organizational culture, career development, work motivation and job satisfaction of the employees of the Public Housing Service of the Settlement Areas and Human Settlements of Sumenep Regency; 2) Test and analyze the relationship of influence simultaneously which is significant organizational culture, career development and work motivation on job satisfaction of employees of the Department of Housing and Human Settlements, Sumenep Regency; 3) Test and analyze the relationship between the influence of organizational culture and job satisfaction of employees of the Public Housing Service of the Settlement Areas and Human Settlements of Sumenep Regency. 4) Test and analyze the relationship between the influence of career development and job satisfaction of the employees of the Public Housing Service for Settlement Areas and Human Settlements of Sumenep Regency; 5) Test and analyze the relationship between the influence of work motivation and job satisfaction of employees of the Public Housing Service of the Settlement Areas and Human Settlements of Sumenep Regency.